2009
DOI: 10.1093/ndt/gfp292
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium homeostasis in patients with early stagesof chronic kidney disease: effects of vitamin D3 supplementation

Abstract: Our results demonstrate that (1) [Ca(2+)](i), intracellular calcium stores and the capacitative calcium entry were significantly increased already in early stages of CKD; (2) long-term vitamin D(3) supplementation normalized [Ca(2+)](i) without any effect on intracellular calcium reserves or the capacitative calcium entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 25 publications
2
30
0
1
Order By: Relevance
“…Many studies have evaluated vitamin D (either cholecalciferol or ergocalciferol) as a treatment for vitamin D insufficiency or SHPT in adults with predialysis CKD [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]. Most were open-label studies and some were conducted in patients exhibiting SHPT.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated vitamin D (either cholecalciferol or ergocalciferol) as a treatment for vitamin D insufficiency or SHPT in adults with predialysis CKD [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]. Most were open-label studies and some were conducted in patients exhibiting SHPT.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we demonstrated that calcitriol, an active metabolite of vitamin D, prevents Ca 2+ increase through P2X 7 channels and reduces the membrane permeability through P2X 7 pores [13] . Moreover, vitamin D 3 supplementation in early stages of CKD decreased [Ca 2+ ] i but did not affect intracellular calcium reserves and calcium entry through CRAC channels [10] . These findings point to the potential role of P2X 7 receptors in enhanced [Ca 2+ ] i in this disease.…”
Section: Discussionmentioning
confidence: 90%
“…[25,26] , by the enhanced calcium influx [9] and the increase in intracellular calcium reserves [10] . The main mechanism of the lymphocyte [Ca 2+ ] i increase involves CRAC channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBMC were isolated from heparinized blood of healthy volunteers by Ficoll gradient centrifugation, diluted 1:1 with RPMI-1640 medium, layered onto an equivalent volume of medium LSM-1077 and centrifuged at 700G for 20 min at 20°C, as previously reported [7]. The PBMC layer was washed in 40 ml RPMI, resuspended in 10 ml RPMI and 10% fetal bovine serum (FBS), centrifuged for 10 min at 300g and 22°C.…”
Section: Preparation Of Pbmcmentioning
confidence: 99%